Sphincter of Oddi Function and Risk Factors for Dysfunction - Afghani, Elham; Lo, Simon K.; Covington, Paul S.; Cash, Brooks D.; Pandol, Stephen J. (Frontiers in Nutrition, 2017)
The sphincter of Oddi (SO) is a smooth muscle valve regulating the flow of biliary and pancreatic secretions into the duodenum, initially described in 1887 by the Italian anatomist, Ruggero Oddi. SO dysfunction (SOD) is a broad term referring to numerous biliary, pancreatic, and hepatic disorders resulting from spasms, strictures, and relaxation of this valve at inappropriate times. This review brings attention to various factors that may increase the risk of SOD, including but not limited to: cholecystectomy, opiates, and alcohol. Lack of proper recognition and treatment of SOD may be associated with clinical events, including pancreatitis and biliary symptoms with hepatic enzyme elevation. Pharmacologic and non-pharmacologic approaches are discussed to help recognize, prevent, and treat SOD. Future studies are needed to assess the treatment benefit of agents such as calcium-channel blockers, glyceryl trinitrate, or tricyclic antidepressants in patients with SOD.